Major Ice Sheet Change in the Weddell Sea Sector of West Antarctica Over the Last 5, 000 Years. (6th November 2019) - Siegert, Martin J.; Kingslake, Jonathan; Ross, Neil; Whitehouse, Pippa L.; Woodward, John; Jamieson, Stewart S. R.; Bentley, Michael J.; Winter, Kate; Wearing, Martin; Hein, Andrew S.; Jeofry, Hafeez; Sugden, David E.
Abstract: Until recently, little was known about the Weddell Sea sector of the West Antarctic Ice Sheet. In the last 10 years, a variety of expeditions and numerical modelling experiments have improved knowledge of its glaciology, glacial geology and tectonic setting. Two of the sector's largest ice streams rest on a steep reverse‐sloping bed yet, despite being vulnerable to change, satellite observations show contemporary stability. There is clear evidence for major ice sheet reconfiguration in the last few thousand years, however. Knowing precisely how and when the ice sheet has changed in the past would allow us to better understand whether it is now at risk. Two competing hypotheses have been established for this glacial history. In one, the ice sheet retreated and thinned progressively from its Last Glacial Maximum position. Retreat stopped at, or very near, the present position in the Late Holocene. Alternatively, in the Late Holocene, the ice sheet retreated significantly upstream of its present grounding line and then advanced to today's location due to glacial isostatic adjustment and ice shelf and ice rise buttressing. Both hypotheses point to data and theory in their support yet neither has been unequivocally tested or falsified. Here we review geophysical evidence to determine how each hypothesis has been formed, where there are inconsistencies in the respective glacial histories, how they may be tested or reconciled, and what new evidence is required to reach a common model for the Late Holocene ice sheet history of the Weddell Sea sector of West Antarctica. Plain Language Summary: The West Antarctic Ice Sheet is vulnerable to climate and ocean warming because it rests on a bed more than 2 km below sea level in some places. Understanding how this ice sheet has changed in the recent past guides our appreciation of how it will change in the near future. Getting such information requires measurement of (1) structures in the ice that reflect former ice sheet change; (2) the age when rock surfaces were most recently exposed or covered by ice; and (3) computer calculations of ice sheet processes to understand what change is realistic. The ice sheet was certainly a lot bigger during the ice age, about 20, 000 years ago, but two alternative histories exist on how it shrank to today's size in the last 5, 000 years. In one, the ice sheet gets smaller gradually over time, and in the other the ice sheet becomes smaller than today before it expands to its current position. Arriving at a single history for the ice sheet may allow us to better understand whether to expect change to occur here in future and how it may happen. Key Points: The Weddell Sector has experienced major change since the Late Holocene It is unclear whether the ice sheet gradually shrank to its modern size from its full‐glacial state or became smaller here and then regrew Targeted geophysical dating of buried and exposed surfaces and sediment drilling may resolve the inconsistencies in glacial history